2018
DOI: 10.1155/2018/3823426
|View full text |Cite
|
Sign up to set email alerts
|

Stevia Prevents Acute and Chronic Liver Injury Induced by Carbon Tetrachloride by Blocking Oxidative Stress through Nrf2 Upregulation

Abstract: The effect of stevia on liver cirrhosis has not been previously investigated. In the present study, the antioxidant and anti-inflammatory properties of stevia leaves were studied in male Wistar rats with carbon tetrachloride- (CCl4-) induced acute and chronic liver damage. Acute and chronic liver damage induced oxidative stress, necrosis, and cholestasis, which were significantly ameliorated by stevia. Chronic CCl4 treatment resulted in liver cirrhosis, as evidenced by nodules of hepatocytes surrounded by thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…Several studies have demonstrated the pharmacological properties of Stevia rebaudiana Bertoni as a hepatoprotector and mainly as an antifibrotic agent (Ramos‐Tovar, Buendia‐Montaño, et al, ; Ramos‐Tovar, Flores‐Beltrán, et al, ; Ramos‐Tovar, Hernández‐Aquino, et al, ). However, few studies have been performed to evaluate the related pharmacological effects of its secondary compounds, such as Reb A (Holvoet et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the pharmacological properties of Stevia rebaudiana Bertoni as a hepatoprotector and mainly as an antifibrotic agent (Ramos‐Tovar, Buendia‐Montaño, et al, ; Ramos‐Tovar, Flores‐Beltrán, et al, ; Ramos‐Tovar, Hernández‐Aquino, et al, ). However, few studies have been performed to evaluate the related pharmacological effects of its secondary compounds, such as Reb A (Holvoet et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Brown staining of proteins on the tissue was considered a positive reaction. Digital images of the histological sections were collected, and a positive signal was quantified by using ImageJ ® software (NIH, MD, USA) (Ramos‐Tovar, Hernández‐Aquino, et al, ). Appropiate controls to prove the specificity of primary antibodies have been performed by other authors (Eissa, Kenawy, El‐Karef, Elsherbiny, & El‐Mihi, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Stevia rebaudiana (stevia), which is a small perennial shrub from Paraguay, has exhibited important antioxidant and anti‐inflammatory properties that suggest that this plant can be an effective antifibrotic and anticirrhotic remedy (Ramos‐Tovar & Muriel, ). Our previous report shows that stevia upregulates Nrf2, which counteracts oxidative stress, and prevents inflammation by inhibiting NF‐κB in CCl 4 ‐cirrhotic rats (Ramos‐Tovar et al, ). However, the effects of stevia on liver fibrogenesis remain unstudied.…”
Section: Introductionmentioning
confidence: 96%
“…Several medicinal plants have been extensively used in the traditional system of medicine for the management of liver diseases. Because cirrhosis is a major health problem throughout the world, and due to the lack of effective treatments, several studies have suggested that the use of medicinal herbs and phytochemicals could protect against liver damage by several mechanisms, such as the inhibition of oxidative damage, inflammation, and fibrogenesis (Casas‐Grajales et al, ; Hernández‐Aquino et al, ; Ramos‐Tovar et al, ). In this regard, Stevia rebaudiana (stevia), which is a small perennial shrub from Paraguay, has exhibited important antioxidant and anti‐inflammatory properties that suggest that this plant can be an effective antifibrotic and anticirrhotic remedy (Ramos‐Tovar & Muriel, ).…”
Section: Introductionmentioning
confidence: 99%